MEMORANDUM IN OPPOSITION TO AB 2200, THE "FIRE-SAFE CIGARETTE ACT OF 980000" (Tufts Archival Research Center, 2007)
Memo opposing a new bill which would require the California state fire marshall to implement state fire safety codes by 1999. Claims that there is not enough money to fund the needed research for this nor is there a plan to account for the loss in excise taxes from anticipated decreased cigarette sales. Cites statisicis regarding cigarette related fires which support the argument that no new legislation is needed.